Assessing Carbon Carrying Capacity of Forest Ecosystem: A Case Study in West Sumatera Province - Rahmadini, Shintia (Universitas Andalas, 2025)
All attempts have been taken by majority nations to reduce and invent the greenhouse gases (GHG) emission, but none of them provide any quantitative framework to assess ecosystem capacity for carrying carbon. To measure ecosystem boundaries to offset carbon and how far the emission has exceeded beyond them, this paper aims to calculate the carbon carrying capacity and evaluate its availability to sequester CO2 emission in a certain area. Considering forests, the major carbon reservoir to be the key ecosystem and taking West Sumatera Province in Indonesia as the case study, the Carbon Carrying Capacity (CCC) assessment is conducted with ecological footprint concept through carbon capacity surplus-deficit. The results show the forest CCC was fluctuated which were the highest 3.9 million ton in 2016 and the lowest 2.4 million ton in 2019, and primary mangrove land cover was the biggest carbon sequesters for 114 ton C/ha every year. The forest CCC was dominantly deficit which interpreted as limited and unavailable forest capacity to offset carbon emission. To improve forest CCC, forest area needs to be conserved, also develop low-carbon and green economic transformation to reduce GHG emission. The local society can take role to conserve the forest through customary laws application, then the government ought to plan spatial strategies through limiting land use for the primary forest and prohibiting mangrove and swamp forest conversion, also monitor, control and make legal approach to achieve national targets on reducing CO2 emission.